A NIR‐Responsive Phytic Acid Nickel Biomimetic Complex Anchored on Carbon Nitride for Highly Efficient Solar Hydrogen Production. (14th January 2021) - Huang, Yuanyong; Jian, Yaping; Li, Longhua; Li, Di; Fang, Zhenyuan; Dong, Weixuan; Lu, Yahui; Luo, Bifu; Chen, Ruijie; Yang, Yingchen; Chen, Min; Shi, Weidong
Abstract: A challenge in photocatalysis consists in improving the efficiency by harnessing a large portion of the solar spectrum. We report the design and realization of a robust molecular‐semiconductor photocatalytic system (MSPS) consisting of an earth‐abundant phytic acid nickel (PA‐Ni) biomimetic complex and polymeric carbon nitride (PCN). The MSPS exhibits an outstanding activity at λ =940 nm with high apparent quantum efficiency (AQE) of 2.8 %, particularly λ>900 nm, as it outperforms all reported state‐of‐the‐art near‐infrared (NIR) hybrid photocatalysts without adding any noble metals. The optimum hydrogen (H2 ) production activity was about 52 and 64 times higher with respect to its pristine counterpart under the AM 1.5 G and visible irradiation, respectively, being equivalent to the platinum‐assisted PCN. This work sheds light on feasible avenues to prepare highly active, stable, cheap NIR‐harvesting photosystems toward sustainable and scalable solar‐to‐H2 production. Abstract : An artificial photocatalysis system consisting of a carbon nitride polymer and phytic acid nickel biomimetic complex has been successfully constructed. It was adopted as an active and stable NIR harvesting photosystem toward scalable solar‐to‐H2 production.